Identification of soil-structure interaction effects based on geodetic monitoring of a railway bridge - Psimoulis, Panos; Stiros, Stathis; Moschas, Fanis (2014)
The monitoring of bridges using geodetic methodologies permits the direct measurement of displacements and potential identification of effects of soil-structure interaction. In this study the response of the historical Gorgopotamos railway (Central Greece) has been measured using a Robotic Total Station (RTS) during the passage of trains on different times of the year and under various soil conditions. The measurements revealed that the initial impact response of the deck to the train loading presents differences which seem to correlate with the differences in the moisture content of the bridge foundation ground.